1918
DOI: 10.1002/prac.19180980123
|View full text |Cite
|
Sign up to set email alerts
|

Die Baeyersche Spannungstheorie und die Struktur des Diamanten

Abstract: ~-~-') Vgl. die-gleichlautende Mittdung in den Sitzungsberichten der Heidelberger Akademie der Wissenschaften, Stiftnng H e i n r i c h Jd an z, math.-naturwiss. Klasse, A b t d u n g A, Jahrgang 1915, 7. Abhandlung. 2) Bex. 18, 2277 (1885). 31* ') S a c h s e , %. f. physik. Chem. 11, 202 (1893) FuBnote:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

1930
1930
2004
2004

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(23 citation statements)
references
References 28 publications
0
20
0
3
Order By: Relevance
“…If there are more than two bonds that qualify by rule 2, those that generate the fewest new rings are given priority. 4. Bonds at heteroatoms are strategic.…”
Section: Strategic Bonds and Substructures Relevant For Synthesesmentioning
confidence: 98%
“…If there are more than two bonds that qualify by rule 2, those that generate the fewest new rings are given priority. 4. Bonds at heteroatoms are strategic.…”
Section: Strategic Bonds and Substructures Relevant For Synthesesmentioning
confidence: 98%
“…J. Org and Ernst Mohr's [38] ideas about the non-planarity of the cyclohexane ring. Just as Emil Fischer had used the strainfree tetrahedron as a building block for strain-free aldohexoses and observed agreement between the experimentally obtained and theoretically expected number of stereoisomers, Windaus anticipated two non-strained stereoisomers with the constitution of decalin (Scheme 6).…”
mentioning
confidence: 99%
“…Sachse reported that two nonplanar models of cyclohexane-conformations as they were called later-do not require bending of the tetrahedral angle,[671 a discovery which was exploited and extended to larger rings by E. Mohr. 1681 In 1905 bending at all; on the other hand, the deflection of the bond angles in smaller and larger rings-assumed to be Among the chemists to whom Baeyer introduced scientific thinking and the art of experimentation were: G. uon Briining, W . Dieckmann, C. Duisberg, E. Fischer, 0.…”
mentioning
confidence: 99%